School-based mental health promotion-interventions for adolescent in low and middle income countries: systematic review and meta-analysis of mental health outcomes from randomised controlled trials - Rahima Dahlan @ Mohd Shafie
Background: Most of the effectiveness evidence for school-based mental health promotion interventions for adolescent derives from high income countries (H IC). However, evidence transferability to diverse-culture and low-resource situation with specialists of mental health is yet to be explored. Objective: This paper presents a comprehensive review and the assessment of randomised controlled trials (RCT) for mental health promotion interventions at schools associated to adolescents from low- and middle-income countries (LMICs). Method: Meta-analysis and a comprehensive review were conducted from April until June 2018 by using several databases, such as PubMed, Scopus, Cochrane, lSI Web of Knowledge, OVID, and reference lists. The studies were assessed using the Cochrane's Risk of Bias (RoB) tool, along with random effects models. Results: From the 12 selected studies, only 11 were included in meta-analysis with 4701 and 7046 participants in positive and negative mental health groups, respectively. Across primary outcomes, the overall effect sizes were insign ificant for both positive mental health (SMD 0.10, 95% CI -0.04 to 0.24) and negative mental health (SMD -0.09, 95% CI -0.21 to 0.02). The subgroup analysis displayed insignificant effect sizes for all indicators of positive mental health (prosocial behaviour, sense of hope, and coping) and negative mental health (posttraumatic symptom, depression, and anxiety). Besides, there was considerable heterogeneity (/2 range: 41 %-93%). Most studies indicated predominantly high risk in detection and performance bias due to non-blinding. Conclusions: Evidence from the RCTs of adolescent school-based mental health promotion interventions in LMIC incorporated in this study failed to display much improvement in results for mental health. Future efforts should adopt a study design that is rigorous to address bias ness and to implement interventions with cultural and contextual adaptation in low-resource settings. Keywords: adolescent, low and middle income countries, mental health promotion, meta-analysis